New SPARC research on ‘Peace with Nature’ supports the UN Convention on Biological Diversity - Ba, Baba; Nanteza, Patricia (CGIAR System Organization, 2024)
Supporting Pastoralism and Agriculture in Recurrent and Protracted Crises (SPARC) has developed new research that seeks to better understand how examples like the Ferlo Silvopastoral Reserve and other local NRM initiatives including ‘conventions locales’ (local agreements between NRM users) in West Africa and participatory rangeland management (PRM) in East Africa can contribute more explicitly to peacebuilding.